Are social support and HIV coping strategies associated with lower depression in adults on antiretroviral treatment?: Evidence from rural KwaZulu-Natal, South Africa - Yeji, Francis; Klipstein-Grobusch, Kerstin; Newell, Marie-Louise; Bärnighausen, Till (AIDS care, 2014)
We assess depression rates and investigate whether depression among HIV-infected adults receiving antiretroviral treatment (ART) is associated with social support and HIV coping strategies in rural South Africa (SA). The study took place in a decentralised public-sector ART programme in a poor, rural area of KwaZulu-Natal, SA, with high-HIV prevalence and high-ART coverage. The 12-item General Health Questionnaire (GHQ12), validated in this setting, was used to assess depression in 272 adults recently initiated on ART. Estimates of depression prevalence ranged from 33% to 38%, depending on the method used to score the GHQ12. Instrumental social support (providing tangible factors for support, such as financial assistance, material goods or services), but not emotional social support (expressing feelings, such as empathy, love, trust or acceptance, to support a person), was significantly associated with lower likelihood of depression [adjusted odds ratio (aOR) = 0.65, 95% confidence interval (CI) 0.52-0.81,P< 0.001], when controlling for sex, age, marital status, education, household wealth and CD4 cell count. In addition, using “avoidance of people” as a strategy to cope with HIV was associated with an almost three times higher odds of depression (aOR = 2.79, CI: 1.34-5.82,P= 0.006), whereas none of the other five coping strategies we assessed was significantly associated with depression. In addition to antidepressant drug treatment, interventions enhancing instrumental social support and behavioural therapy replacing withdrawal behaviours with active HIV coping strategies may be effective in reducing the burden of depression among patients on ART.